Craniofacial Cleft: A Case of Tessier 10 Cleft With a Novel Method to Repair Large Bilateral Colobomas. (November 2019) - Barnett, Joshua M.; Pang, John H. Y.; Herman, Sean; Lee, Jonathan; Stefko, S. Tonya; Losee, Joseph E.; Goldstein, Jesse
Objective: To describe a reliable method utilizing large, rotation flaps to reconstruct a number 10 Tessier cleft. Design: This is a descriptive clinical case report. Setting: Pediatric teaching hospital affiliated with a university. Patients, Participants: One participant in this clinical case report. Interventions: Full-thickness excision of the clefted eyelid, brow, and forehead tissue was performed bilaterally to develop medial and lateral eyebrow and forehead flaps. Right: the forehead/brow flap was rotated caudally to reapproximate the eyebrow and an eyelid rotation flap was also used to reapproximate the lid margin. Left: forehead/brow rotation flap allowed realignment of the eyebrow and a series of Z-plasties were used in the eyelid to reapproximate the lid margin and to lengthen the eyelid. Main Outcome Measure(s): Develop and construct a reliable reconstruction with full-eyelid closure and minimal donor site morbidity. Results: Complete eyelid closure bilaterally was achieved intraoperatively, and was maintained at 6-month follow-up with no evidence of ocular pathology. Conclusions: Large, bilateral upper eyelid colobomas require repair to prevent blindness. Although free tarsomarginal grafts and lid-sharing procedures have been described, we demonstrate that large rotation flaps designed along the cleft margin can provide a reliable reconstruction and minimize donor-site morbidity.